Analisis Pendapatan Petani Padi Varietas Inpari 37 di Loka Penelitian Penyakit Tungro - Rezeki M; Muh Ikbal Putera; Nurhaeda Nurhaeda (Jurnal Agribis, 2024)
This research aims to determine business income and business feasibility. This research was carried out at the Panca Rijang District Disease Research Center, Sidenreng Rappang Regency from March to April 2023. This research uses observation techniques, interviews and questionnaire techniques. Meanwhile, the sample was determined by taking 5 people involved in cultivating Inpari 37 variety rice. The data analysis used descriptive data analysis. The results of the research show that the average total costs (fixed costs and variable costs) incurred as a whole amounted to Rp. 10,337,233 and the income obtained by all respondents was Rp. 29,548,800 and the income generated by all respondents was Rp. 19,211 ,568. The R/C Ratio obtained was 2.86 which shows that the business is profitable and worth pursuing.